Human Capital Investment and Employment Growth in Nigeria - J. O. Saka (Theory, Methodology, Practice, 2020)
This paper mainly examines the link between human capital investment and employment growth in Nigeria for the period spanning 1980–2019 using timeseries data. The theoretical model is rooted in the simple theory of investment in human capital based on Ashton and Green (1996) relating to maximization of lifetime earnings and wealth. Diagnostic tests show that the ordinary least square (OLS) estimation technique is plausible. Results show that employment rate can positively induce government expenditure on education and health and secondary school enrollment.Creation of investment opportunities through basic infrastructural facilities – electricity, roads,etc. – is key to employment growth and human capital investment.